Study on intermetallic compound formation and growth at the solder joint interface during laser soldering using sn-ag-cu powdered compact solder on copper pad - Nabila, Tamar Jaya (2024)
Laser technology has been applied in the electronic soldering for many years as one of its advantages known is the ability to set the process parameters to suit the individual solder joint requirements. This method of joining, ease the automation compared to the reflow soldering process which is the common soldering technique used in industries. Aside from it is time-saving soldering, it also enables the delivery of a large amount of energy to specific locations (localized), even when the place is difficult to reach. Its rapid cooling rate advantage also contribute to positive impact on the thickness of intermetallic compound (IMCs) formation at the solder joint interface. Meanwhile, the powder metallurgy (PM) method is the latest fabrication process to produce lead-free composite solder alloys. fabricating the solder alloy through PM method is said to be able to improve lead-free solder mechanical and solderability properties plus more economical as the alloy is produced with low energy consumption. Therefore, as from previous studies it is found that, fabricating solder through PM method and solder by using laser technology did have an improvement on the solder joint strength and the thickness of IMCs. Thus, this research, these two findings are combined to get a better solder joint performance. This study aims at determining the IMCs formation and growth at the interface of Sn3Ag0.5Cu (SAC305) solder alloy and copper substrate after laser soldering. Emphasis was made on the effect of laser parameters, subsequent ageing of solder joints on the interfacial microstructures and their effects toward solder joint strength. Specimens were prepared through powder metallurgy with the size of 6 mm in diameter and 1 mm of thickness. Then, they were subjected to laser soldering with various parameters used such as laser power, scanning time and defocus offset distance. The process was followed by ageing at the temperature of 150oC until 2000 hours and shear test following ASTM F1269. Several techniques of materials characterization including optical, image analysis, scanning electron microscopy and energy dispersive X-ray analysis were used to examine and quantify the intermetallics in terms of composition, thickness and morphology. Results showed that IMCs formed at the interface was Cu6Sn5 after laser soldering with the thickness of 1.509 μm and this value increasing when laser power/scanning time/defocus offset length was increasing. Their maximum shear load was 0.62 kN and this was supported by wetting angle of 36.18° which explains the lower wetting angle, the higher solder joint strength will be. When exposed to ageing, another IMC was formed which was Cu3Sn between Cu6Sn5 and copper substrate for the rest (500H,1000H & 2000H). These IMC was also found to be increasing upon ageing duration. The maximum IMC thickness obtained for SAC305 powder compacted after 2000 H of aged was 13.147 μm meanwhile, the maximum IMC thickness obtained after 2000 H of aged for the wire was 13.947 μm. Meanwhile, solder joint strength showed a decreasing trend towards ageing duration due to its brittle nature and easy to break. In terms of solder powder and wire, it was found that solder made from powder gave better performance in terms of strength, 28.51 MPa and IMCs thickness, 3.1635 μm. Thus, an improvement in quality has been observed for combining the technology of fabricating a solder through PM method and soldering by using laser technology.